Pathogenic and Genetic Characteristics of Helicobacter Pylori, and its Relationship with Drug-Resistance - Nilgün Uyduran Ünal; Adnan Barutçu; Toğrul Nagiyev; Mehmet Ağın; Tülay Kandemir; Oğuz Üsküdar; Figen Doran; Fatih Köksal; Gökhan Tümgör (Gazi Medical Journal)
Objective: This study aimed to determine the epidemiological characteristics of Helicobacter pylori (H. pylori) infection at the genotype level in patients presenting with dyspeptic complaints, and to show the distribution of virulence factors, importance of intrafamilial transmission, as well as the distribution of resistance to macrolide and quinolone antibiotics. Methods: The study comprised 110 patients with dyspeptic complaints who were admitted to our hospital between January 13, 2015, and December 31, 2016. Through histopathology, culture, and glmM-polymerase chain reaction (PCR) techniques, we detected H. pylori. The vacA, cagA, and cagE genes were determined in patients with positive PCR results were positive. Results: H. pylori strains and clinical results were not found to be significantly correlated in the study. Both genetic variants A2142G and A2143G were discovered to be present in the individuals. Eight patients had clarithromycin resistance (34.7%). All patients with a positive A2142G mutation and 55% of patients with a positive A2143G mutation were found to have clarithromycin resistance. Levofloxacin resistance was present in only one (4.3%) patient who could produce H. pylori in culture. Conclusion: Approximately 1/3 of the children with dyspeptic complaints were positive for H. pylori infection. The most common genotype was observed to be vacAs2. Even individuals with at least one of the genetic mutations A2142G and A2143G have the potential for antibiotic resistance. High resistance was found against clarithromycin in the standard triple therapy regimen used in children for treating H. pylori infection.